Excited Heavy Mesons From Lattice QCD - Thomas, Christopher (American Institute of Physics Publishing, 2019)
I discuss some recent investigations of excited mesons using first-principles lattice QCD calculations. Over the last few years we have made significant advances in studying near-threshold states, resonances and related scattering phenomena. I illustrate this progress by presenting results from scattering channels involving charm mesons, including DK scattering relevant for the enigmatic Ds(2317) and DK scattering. I also comment on applications to other channels and future prospects.